PvPGIP2 Accumulation in Specific Floral Tissues But Not in the Endosperm Limits Fusarium graminearum Infection in Wheat - Silvio Tundo; Michela Janni; Ilaria Moscetti; Giulia Mandalà; Daniel Savatin; Ann Blechl; Francesco Favaron; Renato D’Ovidio (Molecular Plant-Microbe Interactions, 2016)
Fusarium head blight (FHB) caused by Fusarium graminearum is one of the most destructive fungal diseases of wheat worldwide. The pathogen infects the spike at flowering time and causes severe yield losses, deterioration of grain quality, and accumulation of mycotoxins. The understanding of the precise means of pathogen entry and colonization of floral tissue is crucial to providing effective protection against FHB. Polygalacturonase (PG) inhibiting proteins (PGIPs) are cell-wall proteins that inhibit the activity of PGs, a class of pectin-depolymerizing enzymes secreted by microbial pathogens, including Fusarium spp. The constitutive expression of a bean PGIP (PvPGIP2) limits FHB symptoms and reduces mycotoxin accumulation in wheat grain. To better understand which spike tissues play major roles in limiting F. graminearum infection, we explored the use of PvPGIP2 to defend specific spike tissues. We show here that the simultaneous expression of PvPGIP2 in lemma, palea, rachis, and anthers reduced FHB symptoms caused by F. graminearum compared with symptoms in infected nontransgenic plants. However, the expression of PvPGIP2 only in the endosperm did not affect FHB symptom development, indicating that once the pathogen has reached the endosperm, inhibition of the pathogen’s PG activity is not effective in preventing its further spread.